Global, national, and local approaches to mental health: examples from India - Mitchell G. Weiss, Mohan Isaac, Shubhangi R. Parkar, Arabinda N. Chowdhury and R. Raguram (Tropical Medicine and International Health volume no 1 pp 4-23 january 2001, 2001)
Neuropsychiatric disorders and suicide amount to 12.7 per cent of the global burden of disease and related conditions (GBD) according to World Health Organization (WHO) estimates for 1999, and recognition of the enormous component of mental illness in the GBD has attracted unprecedented attention in the reld of international health. Focusing on low- and middle-income countries with high adult mortality, this article discusses essential functions of international agencies concerned with mental health. A review of the history and development of national mental health policy in India follows, and local case studies consider the approach to planning in a rural mental health programme in West Bengal and the experience in an established urban mental health programme in a low-income community of Mumbai. Local programmes must be attentive to the needs of the communities they serve, and they require the support of global and national policy for resources and the conceptual tools to formulate strategies to meet those needs. National programmes retain major responsibilities for the health of their country's population: they are the portals through which global and local interests, ideas, and policies formally interact. International priorities should be responsive to a wide range of national interests, which in turn should be sensitive to diverse local experiences. Mental health actions thereby benert from the synergy of informed and effective policy at each level.